A dual domain systematic review and meta-analysis of risk tool accuracy to predict cardiovascular morbidity in prehypertension and diabetic morbidity in prediabetes - William J. Waldock; Nicholas Tekkis; Joe Zhang; Hutan Ashrafian (Frontiers in Endocrinology, 2025)
ObjectiveHealth forecasting predicts population trends through risk prediction algorithms which can estimate the risk of future disease developing. Screening algorithms can systematically identify patients with a high probability of undiagnosed diseases for diagnostic testing. We describe a dual domain systematic review and meta-analysis of the accuracy of available risk tools to (1) predict prehypertensive deterioration to cardiovascular morbidity, & (2) predict prediabetes deterioration to diabetic morbidity.Materials and MethodsThe primary outcome was the accuracy of the risk scores, and the secondary outcomes were the reporting quality and risk of bias. The dual domain systematic review included studies involving risk tools for (1) prehypertensive adults to predict cardiovascular morbidity (including hypertension, stroke and coronary heart disease) and (2) prediabetic adults to predict diabetic morbidity (including Type 2 Diabetes and end organ damage, such as diabetic nephropathy). Following PROSPERO registration (IDs 425686 & 425683), searches were conducted in PubMed, MEDLINE and Google Scholar.ResultsAccuracy of risk prediction in prehypertension and prediabetes was high: the pooled C statistic for All Cause Cardiovascular Disease was 0.77 (CI 0.71, 0.84) and the pooled Sensitivity for All Cause Diabetic Disease Spectrum risk was 0.68 (CI 0.65, 0.7). However, we found high risk of bias, with inconsistent reporting in both prehypertension and prediabetes papers.DiscussionWe propose nine recommendations for policymakers and commissioners, organised under an “A to I” framework.ConclusionWe found that predictive performance was generally accurate. However, there remain limitations due to methodological inconsistency, such as timeframe, which undermines comparison.